Relasi Gender dan Pendidikan Islam - Rohmah, Nur; Ulinnuha, Labib (Jurnal Pendidikan Islam, 2014)
The concept of equality of men and women or feminism concept offered by the West, and it can not be accepted by most people, especially the Muslim community. This is because the legitimacy of religious dogma, which is unbalanced and disposed to the side with men, which is adopted by most Muslims, has been going on up to now. The concept of equality between men and women are expected by Islam can be obtained by further examining the guidelines of Islam (Al-Quran and Al-Hadis). The concept of equality that is desired by Islam, that is inspired from the equation in terms of creation, function and position in the world and freedom of tawheed and worship to the God among men and women